Virtual Social Network Communication during the Covid-19 Pandemic According To Muslim Community in Sabah (2019-2021) - Ahmad Tarmizi Abdul Rahman; Nor-Ina Kanyo; Santi Hairuddin (AnKa Publisher, 2022)
Nowadays, Virtual social network communication is one of medium technological advancement in the field of information and communication. The use of virtual communication risen since the COVID-19 started in Wuhan 2019. The pandemic has changed the lifestyle of the Muslim community in Sabah, especially related to the use of virtual social media such as Facebook, Instagram, Whatsapp and Twitter. The use of virtual social networks interrupted the local community stability communication life if it usage does not paralleled to ethics, religion and culture sensitivity. This study is a descriptive study that uses a quantitative design and questionnaires as it research instruments. The target respondents for this study are the Muslim communities in Kota Kinabalu, Sabah and it suburbs. The results of the study found that the influence of virtual social network communication media had a great impact on the culture, religion and values of the Muslim community in Sabah. Hence, each Muslim individuals needs to have strong intellectual values to live in the world technological change.